2014
DOI: 10.1073/pnas.1317032111
|View full text |Cite
|
Sign up to set email alerts
|

From a structural average to the conformational ensemble of a DNA bulge

Abstract: Direct experimental measurements of conformational ensembles are critical for understanding macromolecular function, but traditional biophysical methods do not directly report the solution ensemble of a macromolecule. Small-angle X-ray scattering interferometry has the potential to overcome this limitation by providing the instantaneous distance distribution between pairs of gold-nanocrystal probes conjugated to a macromolecule in solution. Our X-ray interferometry experiments reveal an increasing bend angle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 53 publications
3
60
0
Order By: Relevance
“…NMR RDC approaches have proven powerful for probing rotational degrees of freedom, and, in principle, complementary information can be obtained from X-ray scattering interference (XSI), an approach developed by Harbury and colleagues that employs two site-specifically attached Au-nanocrystals and provides an instantaneous distance-probability distribution via the scattering interference pattern of these nanocrystals [35 • ,36 • ,37 • • , Shi et al in press]. Given the large number of sequence combinations in need of exploration, developing information-rich, high-throughput biophysical assays is a key challenge.…”
Section: Rna Helix-junction-helix (Hjh) Elementsmentioning
confidence: 99%
“…NMR RDC approaches have proven powerful for probing rotational degrees of freedom, and, in principle, complementary information can be obtained from X-ray scattering interference (XSI), an approach developed by Harbury and colleagues that employs two site-specifically attached Au-nanocrystals and provides an instantaneous distance-probability distribution via the scattering interference pattern of these nanocrystals [35 • ,36 • ,37 • • , Shi et al in press]. Given the large number of sequence combinations in need of exploration, developing information-rich, high-throughput biophysical assays is a key challenge.…”
Section: Rna Helix-junction-helix (Hjh) Elementsmentioning
confidence: 99%
“…A recent study of bulged duplexes in DNA observed an increase in flexibility of the motifs (a wider range of bend angles was observed) upon an increase in bulge loop size, findings which are broadly consistent with the predictions of oxDNA for the average bend angle distributions. 67 Interestingly, Bailor and co-workers 21,39 have reported results for RNA where the bend angle in bulged RNA duplexes monotonically increased up to about M = 7 and then plateaued. This is again similar to the behavior we see for the oxDNA bend angles for the unstacked configurations, which rises and then plateaus at M = 8.…”
Section: Comparison With Experiments and All-atom Simulationsmentioning
confidence: 99%
“…NMR has been used to study the dynamics of trinucleotide bulge loop structures (Zhang et al 2006(Zhang et al , 2010. X-ray interferometry studies have provided information on the ensemble of bent conformations present in trinucleotide DNA bulge loop constructs (Shi et al 2014).…”
Section: Introductionmentioning
confidence: 99%